PENGARUH DISIPLIN KERJA DAN LINGKUNGAN TERHADAP KINERJA KARYAWAN - Syaifudin Nofrianto; Ade Tiara Yulinda (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to determine the influence of work discipline and the work environment on employee performance at the Bengkulu City Fire and Rescue Service. The independent variables in this study are work discipline (X₁) and work environment (X₂), while the dependent variable is employee performance (Y). This study used a quantitative approach with multiple linear regression. Data were collected through questionnaires distributed to 96 respondents who were active employees of the Bengkulu City Fire and Rescue Service. Data analysis was performed using SPSS. The analysis techniques used included validity and reliability tests, classical assumption tests, multiple linear regression, partial t-tests, simultaneous F-tests, and coefficients of determination (R²). The results of the study indicate that work discipline and the work environment have a positive and significant influence on employee performance. The multiple linear regression analysis yielded the equation Y = 9.204 + 0.421(X₁) + 0.583(X₂), with a coefficient of determination (R²) of 0.593, meaning that 59.3% of the variation in employee performance can be explained by these two variables. The F-test showed that the calculated F-value (67.690) was greater than the F-table (3.09) and a significance level of 0.000 < 0.05, indicating that simultaneously, work discipline and the work environment significantly influence employee performance. Keywords: work discipline, work environment, employee performance